2020
DOI: 10.1177/1053825920923382
|View full text |Cite
|
Sign up to set email alerts
|

Summer Camp: Enhancing Empathy Through Positive Behavior and Social and Emotional Learning

Abstract: Background: Summer camp is proposed as a context to enhance prosocial behavior. This context could be used to apply intervention programs, in addition to being a time of fun and conviviality. A camp-based intervention program to increase empathy was administered for adolescents at risk. Purpose: The aim of this study was to apply and evaluate a positive behavior and social and emotional learning (SEL) intervention on empathy. Methodology/Approach: This exploratory study was carried out with pre–post quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…For instance, there was a big difference in effects for Black and Latinx students in Norton and Watt’s (2014) study, and variation in outcomes was not explained in this study or could not be found in any other related research. Similarly, within the Carpio de los Pinos et al (2020) study, there was a wide range of results across DA (i.e., effects ranging from .00 to .41) and the reason for the range of outcomes was not examined. Furthermore, the review by Gutman and Schoon (2015) shows that the effect sizes for outdoor adventure programs ranged from .18 to .46, but there was no explanation why effects varied across camps.…”
Section: Marginalized Youth and Summer Campsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, there was a big difference in effects for Black and Latinx students in Norton and Watt’s (2014) study, and variation in outcomes was not explained in this study or could not be found in any other related research. Similarly, within the Carpio de los Pinos et al (2020) study, there was a wide range of results across DA (i.e., effects ranging from .00 to .41) and the reason for the range of outcomes was not examined. Furthermore, the review by Gutman and Schoon (2015) shows that the effect sizes for outdoor adventure programs ranged from .18 to .46, but there was no explanation why effects varied across camps.…”
Section: Marginalized Youth and Summer Campsmentioning
confidence: 99%
“…There were no significant changes in fantasy and emotional empathy. The average effect size across the six measures was .20 (Carpio de los Pinos et al, 2020).…”
Section: Marginalized Youth and Summer Campsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous empathy interventions have been carried out with general populations in non-criminological contexts and have proved successful in all age groups. Various promotional, prevention and intervention programmes involving children (Grazzani et al, 2016;Wu et al, 2020), adolescents (Carpio de los Pinos et al, 2020;Ingram et al, 2019) and adults (Leppma & Young, 2016;Romero-Martinez et al, 2016a) have produced significant increases in empathy with a variety of methodologies including teaching, interactive games and mindfulness programmes. Fewer offender empathy programmes have been administered and with various levels of success.…”
Section: The Optimal Conditions For Empathy Interventions For Crime Reductionmentioning
confidence: 99%
“…SEL programmes are designed to help participants to acquire the knowledge, skills, and attitudes to understand and manage emotions (Dusenbury et al, 2015) and to apply them as required in diverse daily situations (Bertrand et al, 2018). For example, Carpio de los Pinos et al (2020) evidence that an SEL summer camp facilitated empathy development in adolescents at-risk for social and emotional problems resultant from negative family circumstances. In another study, a CASEL programme that focused on visual arts and music found significant gains in social awareness and empathy compared to a control group (Mogro-Wilson & Tredinnick, 2020).…”
Section: Location Of Empathy Interventionmentioning
confidence: 99%